AN ETHNOLINGUISTIC PERSPECTIVE ON THE SONG LYRICS OF THE BONET DANCE IN THE SOUTH MIDDLE OF TIMOR REGENCY - Tenis, Amon Bernabas (Prodi. Pendidikan Bahasa Arab, 2024)
This study explores the ethnolinguistic significance of the Bonet dance lyrics within the Dawan community in the South Middle Timor Regency. The Bonet dance, an ancient traditional performance, holds cultural importance for the Dawan people, symbolizing unity, gratitude, respect, and resilience. By analyzing the metaphors and cultural symbols embedded in the lyrics, this research reveals how the Bonet dance preserves and reflects Dawan's values, beliefs, and social structures. The dance expresses key aspects such as the communal spirit, reverence for ancestors, spiritual gratitude, and connection to the land, making it a vital medium for cultural continuity. By examining the lyrics from an ethnolinguistic perspective, this study demonstrates how the Bonet dance contributes to sustaining cultural identity amidst modern influences, ensuring that essential Dawan principles are conveyed across generations